Synthesis of 1,2-Diamines via Hydroamination Reactions - Gupta, Anil K.; Hull, Kami L. (Synlett, 2015)
A brief overview of the synthesis of 1,2-diamines using hydroamination reaction of alkenes is presented herein. In addition, the most recent breakthrough in this field showcasing the intermolecular hydroamination of N-allyl imines is discussed.
Keywords: alkenes; amines; imines; homogeneous catalysis; regioselectivity; diastereoselectivity; metallacycles